ANALISIS MAKNA IKLAN WARDAH DI YOUTUBE - Astini Uyun (Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to find out the meaning in Wardah advertisement on Youtube. In conducting this research researcher used qualitative research methods. The data source of this study is a quote from Wardah ad on Youtube. The data onto this study were obtained two data, primary data and secondary data. Primary data onto this study are in the form of quotes containing lexical, denotative, connotative and contextual meanings. Meanwhile secondary data onto this study is in the form of information relating to Wardah advertisements obtained through Youtube. Data collection techniques in this study include observing Wardah advertisements with the study of meaning (lexical, denotative, connotative and contextual) by downloading video advertisements from Youtube, recording techniques and note taking. Then it is manuscript and analyzed based on the study of meaning. Based on the results of research conducted in analyzing the meaning of Wardah ads on YouTube there are lexical meanings, denotative meanings, connotative meanings and contextual meanings. Lexical meaning there are Indonesian, English and Korean words which are interpreted into Indonesian using a dictionary. The denotative meaning is in the sentences and utterances in Wardah's advertisements. The connotative meaning is in some pictures which have connotation meaning as a form of invitation. Whereas the contextual meaning is in the situation contained in Wardah's advertisement.